Superstitiosi Vates. Nota a un frammento tragico di Ennio (sc. 319 V.2) (ACME, 2023)
On the basis of a forgotten intuition of Alberto Grilli, the article proposes to claim, with new arguments and clarifications, the attribution to a fragment of Ennius’s Telamo of the words superstitiosi uates inpudentesque harioli (Enn. Sc. 319 V.2) which in the more recent editions of Ennian tragedies are instead attributed to Cicero, the source of the fragment.